2005
DOI: 10.1109/tmtt.2005.848767
|View full text |Cite
|
Sign up to set email alerts
|

Multimode cavity efficiency optimization by optimum load location-experimental approach

Abstract: Abstract-In this paper, a novel load-matching procedure for microwave-heating applicators is presented and tested. In order to accomplish the optimization procedure, an optimization method based on the use of the Lebenverg-Marquardt technique has been specifically developed and tested on two different microwave ovens. The proposed procedure allows an efficient optimization of three-dimensional microwave applicators by means of the dielectric sample relocation as a function of its complex permittivity, size, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…6, the point where the reflection coefficient is high). This situation can be shown by means of (23), which has already expressed the power efficiency [2].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, the point where the reflection coefficient is high). This situation can be shown by means of (23), which has already expressed the power efficiency [2].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, it is rather difficult to design an appropriate system according to the material which will be heated in spite of the present numerical methods, and very few studies have been carried out in this field [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…6 and 7 show the online procedure diagram, which consists of sweeping the impedance space by displacing a high-loss dielectric sample inside the cavity over a nylon cartload along the main axis of the oven as described in [17]. Then, for each position of the cartload, both the measured with the VNA and the eight sampled voltage values corresponding to standing wave inside the ten-port are recorded at the computer.…”
Section: B Neural Network Training Methodologymentioning
confidence: 99%
“…7(a), since sample position modification is capable of providing high impedances variations [17]. In this case, the dielectric load has consisted of a 1.5 L sample, which has provided values ranging from 0.1 to 0.8.…”
Section: A Training Procedures and Analysis Of The Neural Structurementioning
confidence: 99%
“…On the other hand, several previous experimental tests have shown that for a multimode microwave cavity, microwave power efficiency varies according to frequency, dielectric properties, position inside the cavity and geometric characteristics of the heated material [7,8]. In fact, in that work it is shown that for several dielectric samples, the efficiency varies with the distance to the magnetron by following a non-linear curve.…”
Section: Introductionmentioning
confidence: 94%